Hyperthermia In Cancer Treatment: A Primer - Baronzio, Gian F.; Hager, E. Dieter; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2006)
Following an introductory overview, Hyperthermia In Cancer Treatment: A Primer comprehensively describes the biological reasons for associating hyperthermia with radiation and chemotherapy and the biological and clinical effects of hyperthermia on cancerous and normal tissues. The volume’s 20 chapters are arranged in three principal parts: physical and methodological studies, biologic principles, and clinical studies.
Physical Aspects of Hyperthermia -- Hyperthermia, Physics, Vector Potential, Electromagnetic Heating -- Thennometry -- Physical Background and Technical Realizations of Hyperthermia -- Thermotherapy and Nanomedicine -- Biological Aspects of Hyperthermia -- Influence of Tumor Microenvironment on Thermoresponse -- Hyperthermia and Angiogenesis -- Vascular Meets of Localized Hyperthermia -- On the Biochemical Basis of Tumour Damage by Hypothermia -- Results of Hyperthermia Alone or with Radiation Therapy and/or Chemotherapy -- Thermo-Chemo-Radiotherapy Association -- A Step Deep on Hyperthermia, Hypoxia and Chemotherapy Interactions -- Clinical Aspects of Hyperthermia -- Locoregional Hyperthermia -- Hyperthermia and Radiotherapy in the Management of Prostate Cancer -- Tumor Ablation Using Radiofrequency Energy -- Cytoreduction, Peritonectomy and Hyperthermic Antiblastic Peritoneal Perfiision for the Treatment of Peritoneal Carcinomatosis -- Hyperthermic Isolated Limb Perfusion -- Intracavitary Hyperthennic Perfusion -- Whole Body Hypothermia at 43.5–44°C -- Extreme Whole-Body Hyperthermia with Water-Filtered Infrared-A Radiation -- Effects of Local and Whole Body Hyperthermia on Immunity -- Fever, Pyrogens and Cancer -- Future Perspectives of Interstitial and Perfusional Hyperthermia.
Keywords: Cancer research; Oncology .; Radiotherapy; Cancer Research; Oncology; Radiotherapy